Transformasi Digital Dalam Proses Bisnis Pendaftaran Mahasiswa Asing UIN Syarif Hidayatullah Jakarta: Implementasi Dan Tantangannya - Evi Muliyah (Bitnet: Jurnal Pendidikan Teknologi Informasi, 2026)
The internationalization agenda of UIN Syarif Hidayatullah Jakarta to increase foreign student enrollment is hindered by a fragmented, semi-manual admission process currently relying on Google Forms without integration into the university’s core academic information system. This study aims to analyze the digital transformation of the foreign student admission business process by mapping the as-is process, identifying challenges from multiple stakeholder perspectives, designing an integrated to-be process model, and examining supporting and inhibiting factors for implementation. A qualitative case study approach was employed, involving in-depth interviews and observations with key informants from the IT center (Pustipanda), academic administration bureau (AAKK), finance bureau, and the international office (PLKI). Findings reveal critical barriers: absence of a dedicated admission portal, regulatory and technical obstacles in foreign currency payment processing, lack of API-based interoperability between systems, cybersecurity risks related to sensitive personal data, organizational resistance to change, and global accessibility issues. The proposed to-be model features a multicurrency payment gateway, digital document submission with auto-validation, single source of truth database, and cloud-based global access. Conclusion highlights that successful transformation requires institutional commitment, regulatory revision, and capacity building. This research contributes practical recommendations for implementing an integrated, user-centric digital admission ecosystem in Islamic public universities.